2003
DOI: 10.1080/00365590310008055
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity in Diagnosis of Bladder Cancer*

Abstract: These results indicate that telomerase activity may be a promising marker for TCC but the technical aspects of the technique must be improved before it is used in routine clinical practice as a standard method. False-negative results obtained using gross hematuric urine should be carefully reevaluated and cell pellets should be washed again and diluted before analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For detection of blad der carcinoma in urine specimens, telomerase proved far more sensitive than cytology or other available screens. The sensitivity of telomerase RT-PCR assay ranged from 75.6% to 94%, compared with 34% to 51% for routine cytology and the specificity ranges from 72% to 100% [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For detection of blad der carcinoma in urine specimens, telomerase proved far more sensitive than cytology or other available screens. The sensitivity of telomerase RT-PCR assay ranged from 75.6% to 94%, compared with 34% to 51% for routine cytology and the specificity ranges from 72% to 100% [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity was increased to 85% for individuals 75 years or younger [34]. A separate study demonstrated similar results with a specificity of 93.5% for the TRAP assay, but a lower sensitivity of 77.4% [35]. For the measurement of the catalytic component of telomerase, hTERT has shown even better results.…”
Section: Telomerasementioning
confidence: 78%
“…55 In one study telomerase activity was found in 77% patients with transitional cell carcinoma of bladder (vs. 6% without). 56 However, in that study, there were no correlation between telomerase activity and the grade or stage of the tumor. The investigators used the TRAP assay to measure telomerase activity in urine cell pellets and noted that presence of gross hematuria was associated with false-negative results, which was resolved by washing and diluting the pellets before the assay.…”
Section: Findings Implicationsmentioning
confidence: 95%